Visual context due to speech-reading suppresses the auditory response to acoustic interruptions in speech - Bhat, Jyoti; Pitt, Mark A.; Shahin, Antoine J. (Frontiers in Neuroscience, 2014)
Speech reading enhances auditory perception in noise. One means by which this perceptual facilitation comes about is through information from visual networks reinforcing the encoding of the congruent speech signal by ignoring interfering acoustic signals. We tested this hypothesis neurophysiologically by acquiring EEG while individuals listened to words with a fixed portion of each word replaced by white noise. Congruent (meaningful) or incongruent (reversed frames) mouth movements accompanied the words. Individuals judged whether they heard the words as continuous (illusion) or interrupted (illusion failure) through the noise. We hypothesized that congruent, as opposed to incongruent, mouth movements should further enhance illusory perception by suppressing the auditory cortex’s response to interruption onsets and offsets. Indeed, we found that the N1 auditory evoked potential (AEP) to noise onsets and offsets was reduced when individuals experienced the illusion during congruent, but not incongruent, audiovisual streams. This N1 inhibitory effect was most prominent at noise offsets, suggesting that visual influences on auditory perception are instigated to a greater extent during noisy periods. These findings suggest that visual context due to speech-reading disengages (inhibits) neural processes associated with interfering sounds (e.g., noisy interruptions) during speech perception.